Dilemmas in language teaching and teacher education - Komorowska, Hanna (Glottodidactica, 2016)
The article analyses disappointing data concerning the status of the teaching profession and teachers’ self-perceptions revealed in recent TALIS, EURYDICE and EUROSTAT reports. Reasons for teachers’ difficulties are then analysed vis-à-vis criteria for the evaluation of quality in education. Emphasis is given to decision-making processes and the type of dilemmas encountered by teacher trainers working in the academic context and foreign language teachers employed in school systems of EU member states. Implications for educational policies of the future are sought and an attempt is made to examine the role of enabling institutions such as the Council of Europe and the European Centre for Modern Languages in Graz.